OPTIMALISASI PEMBELAJARAN TAHSIN MELALUI PENDEKATAN TALAQQI DAN PEER- ASSESSMENT UNTUK MENINGKATKAN KESADARAN KESALAHAN BACAAN AL QUR’AN SISWA SMP IT AN NAJMA - Noor Azida Batubara; Inayatul Mufidah; Ummi Salamah; Wulandari Wulandari; Zhalva Nur Muawalliyah (JURNAL ILMIAH NUSANTARA, 2026)
This Classroom Action Research (CAR) aims to optimize Tahsin learning and improve students' Error Awareness in reading the Qur'an at SMP IT An Najma, which was found to be low in the initial evaluation. Low Error Awareness, characterized by repeated technical errors and dependence on teacher corrections, hinders students' independent learning. The proposed intervention action is the integration of Talaqqi (as a model for standard reading) with Peer-Assessment (as a mechanism for active reflection). This study adopts a spiral Plan-Act-Observe-Reflect Action Research design, carried out in two cycles. The research subjects were seventh-grade students at SMP IT An Najma. Data were collected using reading pre-tests and post-tests (quantitative data), as well as observations and in-depth interviews (qualitative data). Quantitative data analysis focused on the increase in the percentage of learning mastery per cycle, while qualitative data used thematic analysis to identify patterns of improvement in students' self-awareness when assessing their peers. The research results show that the integration of this method is effective. There was a significant improvement in students' reading quality, indicated by the increase in the learning completeness percentage from the initial condition (65%) to 90% at the end of Cycle II. Qualitatively, Peer-Assessment proved to force students to actively analyze the rules of tajwid and articulation points, which in turn enhanced their Error Awareness. Students no longer just receive corrections but are able to identify and correct mistakes in themselves and their peers. It is concluded that the Talaqqi and Peer-Assessment approaches can serve as optimal strategies to enhance students' independence and awareness in Tahsin Al-Qur’an. This study recommends the use of a structured Peer-Assessment rubric as an integral component of the Tahsin curriculum.